2018
DOI: 10.1007/s12053-018-9656-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of energy intensity trend as a tool for long-term forecasting of energy consumption

Abstract: The paper presents retrospective developments of energy intensity of the world economy differentiated by regions and their levels of economic development. The analysis has revealed the persistent decreasing trend in energy intensity across all the macroregions and most countries, showing diversity of its course regarding both the starting point and rate of energy intensity reduction. Based on the time series, it has been shown that energy intensity of an economy is best described by an exponential trend, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The existing body of knowledge acknowledges that energy efficiency enhances environmental quality. In contrast, several research studies have utilized energy intensity as a proxy for a country's overall energy efficiency ( 46 48 ). In their study, Hasanbeigi et al ( 47 ) argued that the primary drawbacks of taking energy intensity as a proxy for a country's energy productivity or efficiency are that the intensity rise may not always correspond to a real increase in the efficiency.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…The existing body of knowledge acknowledges that energy efficiency enhances environmental quality. In contrast, several research studies have utilized energy intensity as a proxy for a country's overall energy efficiency ( 46 48 ). In their study, Hasanbeigi et al ( 47 ) argued that the primary drawbacks of taking energy intensity as a proxy for a country's energy productivity or efficiency are that the intensity rise may not always correspond to a real increase in the efficiency.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…The GDP of individual economies or purchasing power parity (PPP) can drastically change the calculations of energy intensity improvement [34]. It has been suggested that purchasing power parity (PPP) is the most correct approach as it is the real purchasing power of each GDP that will drive the energy use of an economy [51].…”
Section: Energy Intensity (Ei) = Energy/gdpmentioning
confidence: 99%
“…CO 2 emissions were the main contributor to climate change in a period between 1750-2005 [33,34]. A reduction in access to water, food availability, land use are the main threats of climate change to the life expectancy of human populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it represents a large share of the renewable energy in the structure of demand for transport energy. In addition, renewable energy in transport is represented by cars using natural gas and electricity [7]. According to British Petroleum [8], the number of electric vehicles will increase from 1.2 million in 2015 to 100 million in 2035, which is 6% of the world's fleet.…”
Section: Introductionmentioning
confidence: 99%